Integrating Renewable Energy into Railway Systems: A Path to Sustainable Transportation – A Review - Kinda Alshoufi; Khadiga Al-Nagar; Szabolcs Fischer (Chemical Engineering Transactions)
Integrating renewable energy sources into railway systems presents a promising solution to mitigate rising CO2 emissions, growing energy demands, and environmental degradation. This paper reviews the potential of incorporating renewable energy technologies such as solar, wind, bioenergy, and kinetic energy recovery into railway infrastructure. By employing intelligent multi-agent systems to manage rail microgrids, the study demonstrates significant enhancements in energy efficiency, operational cost reduction, and system reliability. Strategic deployment of these energy solutions has shown a potential reduction in energy consumption by up to 30 %. This paper underscores the importance of advanced energy storage and management systems to address the variability of renewable sources, ensuring a stable and consistent energy supply. These findings highlight the critical role of smart grid technologies and AI-driven energy management in advancing the sustainability of railway operations and contributing to global sustainable development objectives.